Educational and therapeutic intervention in children with deforming buccal habits. - Jeny Fernández Martínez; Clotilde de la Caridad Mora Pérez; Raúl López Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Buccal deforming habits are caused by many factors, which make more important the implementation of strategies aimed at reducing their incidence. Objective: To prove the effectiveness of an intervention strategy in children with deforming buccal habits. Methods: An interventional, after-and-before, cuasi-experimental study was developed including 133 children between 5 and 11 years from Abreus municipality. The research was developed in three different periods: diagnosis, interventions and evaluation. The analyzed variables were: deforming buccal habits knowledge including its consequences, age, sex, kind of deforming habit and dental maxillofacial defect. Results: Knowledge about deforming habits increased in children, parents and teachers and 66, 5% of the deforming habits were eradicated, reducing dental maxillofacial defects. Conclusions: The intervention was effective since we could elevate knowledge level on deforming habits and their impact and we could reduce them in a significant percent.